The scientometric evaluation of the institutional research: The Akdeniz universities- part 2 - Konur, Özcan (SILA SCIENCE, 2013)
The scientometric analysis of the research has become one of the most used methods to assess the research performance of the scholars, departments, faculties, universities, countries, and journals in recent years. However, there has not been an extensive scientometric evaluation of the institutional research carried out by the universities in the Akdeniz (Mediterranean) region of Turkey with wide ranging socioeconomic development indices, to examine the development of the research over time. Hence, the purpose of this study was to carry out a scientometric evaluation of the research performed by these universities using three indices in a series of three papers. In the second part of these serial papers, it was found that roughly 70% of the academic staff was from the faculties and departments related to SCIE with wide range of institutional differences. The Akdeniz Universities as a whole had 2% gender deficit in relation to the national the academic force (31% v. 33%) with wide range of institutional differences. The placement of incorrect names for the university name in the affiliation section of the abstract pages of the papers was a serious problem especially for the institutions with more than two words in their names resulting in the lack of visibility in the institutional rankings. There were 18,103 articles and reviews and 97% of these papers were indexed by the SCIE as they were related to Natural and Applied Sciences with strong Social Sciences and Arts and Humanities deficits. "Baskurt OK" from the Department of Physiology of the Akdeniz University was the most prolific author. The top most prolific institution in terms of the number of publications was Cukurova University with the heavy dominance of the SCIE-related papers (98%). The SSCI and A&HCI-related subject dominance was pronounced for the Mehmet Akif Ersoy University, Akdeniz University, and Mersin University. The top university in terms of the H-index was Cukurova University with H-index of 60, closely followed by the Akdeniz University, Mersin University, and Suleyman Demirel University. The results found in the second part of these serial papers suggest that there was a close structure-research performance relationships for these universities hinting the strong effect of the formal and informal rules adapted by these universities on their respective research productivity following North's new institutional theoretical framework. The areas for further research were highlighted.
Keywords: Scientometrics; SCIE; SSCI; Web of Knowledge; Akdeniz Universities; Incentive structures; A&HCI; Research evaluation geography; Research productivity